Metabolic Bone Diseases Affecting Tooth Eruption: A Narrative Review - Christianna Iris Papadopoulou; Iosif Sifakakis; Symeon Tournis (MDPI AG, 2024)
Tooth eruption is an essential process for the development of the oral and maxillofacial system. Several inherited and acquired diseases might affect this tightly regulated process, resulting in premature, delayed, or even failed tooth eruption. The purpose of this article is to review the literature and the clinical parameters of metabolic bone diseases that affect tooth eruption. It examines the physiological aspects of tooth eruption and the pathophysiological changes induced by metabolic bone diseases, including changes in bone metabolism, density, and structure. The search strategy for this review included an electronic search in PubMed, Google Scholar, Medline, Scopus, and the Cochrane Library using the following keywords: "metabolic bone diseases", "tooth eruption", "delayed tooth eruption", and each reported disease in combination with "tooth eruption disorders", covering publications up to March 2024 and limited to English-language sources. Understanding the influence of metabolic bone diseases on tooth eruption is crucial for managing both dental and skeletal manifestations associated with these disorders. This review suggests that a multidisciplinary approach to treatment may significantly improve oral outcomes for patients suffering from such conditions. Clinicians should be aware of the specific dental abnormalities that may arise and consider comprehensive evaluations and individualized treatment plans. These findings underscore the need for further research into targeted therapies that address these abnormalities.